L’écrivain déplacé dans Lolita et Pnin de Vladimir Nabokov - Yannicke Chupin (Revue LISA)
This article focuses on the figure of displaced writers in Vladimir Nabokov’s fiction, and more specifically in Lolita and Pnin. Living the life of exiles affected by permanent instability, the two heroes, Humbert and Pnin, find personal outlets in the writing process. The eccentric language used by both characters displays a form of inventiveness which derives from linguistic disjunction. This article aims at showing in which ways displacement is what sustains the linguistic creativity of these two intellectual exiles.